lim(x-0) x`2-sinx/x+sinx
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 03:32:18
lim(x-0)x`2-sinx/x+sinxlim(x-0)x`2-sinx/x+sinxlim(x-0)x`2-sinx/x+sinxlim(x^2-sinx)/(x+sinx)=lim(2x-c
lim(x-0) x`2-sinx/x+sinx
lim(x-0) x`2-sinx/x+sinx
lim(x-0) x`2-sinx/x+sinx
lim (x^2-sinx)/(x+sinx)
=lim (2x-cosx)/(1+cosx)
=-1/2
lim(x-0) x`2-sinx/x+sinx
求极限lim(x-0) x`2-sinx / x+sinx
lim x趋向0 x^2-sinx/x+sinx
lim(x趋于0)tanx-sinx/x^2=?
lim( 2x-sinx)/(x +sinx)趋近0,
lim (x->0) 3x/(sinx-x)
lim (x→0)x-sinx/x
lim(1-X*X/2)的1/sinX*sinX次方(X趋向0)
(x->0) lim(2x^2-sinx)/x=?
lim(x-0) (sinx/x)^ctg^2(x)
求极限 lim/x-0 (e^x+sinx+x^2)
lim x趋近0sinx/tanx-sinx
lim<x趋近0>√(x^3+x^2)/(sinx+x)=
高数 极限lim(x->0)arccotx/x =如题 lim(x->0)arccotx/x = lim (x->~) sinx/2x =
lim(x→ 0)(tanx-sinx)/xsinx^2
关于lim[x->0,cotx(1/sinx-1/x)中使用无穷小替换的问题lim[x->0,cotx(1/sinx-1/x)=lim[x->0,(cotx/sinx-cotx/x)=lim[x->0,1/sinxtanx]-lim[x->0,1/xtanx](用无穷小替换)=lim[x->0,1/x^2]-lim[x->0,1/x^2]=lim[x->0,1/x^2-1/x^2]=lim[x->0,0]=0 这
lim(x→0)sinx/|x|rt
lim x-sinx/x+sinxx→0